Temporal discrimination is altered in patients with isolated asymmetric and jerky upper limb tremor. Issue 2 (13th November 2019) - Gövert, Felix; Becktepe, Jos; Balint, Bettina; Rocchi, Lorenzo; Brugger, Florian; Garrido, Alicia; Walter, Tim; Hannah, Ricci; Rothwell, John; Elble, Rodger; Deuschl, Günther; Bhatia, Kailash
Abstract: Background: Unilateral or very asymmetric upper limb tremors with a jerky appearance are poorly investigated. Their clinical classification is an unsolved problem because their classification as essential tremor versus dystonic tremor is uncertain. To avoid misclassification as essential tremor or premature classification as dystonic tremor, the term indeterminate tremor was suggested. Objectives: The aim of this study was to characterize this tremor subgroup electrophysiologically and evaluate whether diagnostically meaningful electrophysiological differences exist compared to patients with essential tremor and dystonic tremor. Methods: We enrolled 29 healthy subjects and 64 patients with tremor: 26 with dystonic tremor, 23 with essential tremor, and 15 patients with upper limb tremor resembling essential tremor but was unusually asymmetric and jerky (indeterminate tremor). We investigated the somatosensory temporal discrimination threshold, the short‐interval intracortical inhibition, and the cortical plasticity by paired associative stimulation. Results: Somatosensory temporal discrimination threshold was significantly increased in patients with dystonic tremor and indeterminate tremor, but it was normal in the essential tremor patients and healthy controls. Significant differences in short‐interval intracortical inhibition and paired associative stimulation were not found among the three patient groups and controls. Conclusion: These results indicate that indeterminate tremor, as defined in this study, shares electrophysiological similarities with dystonic tremor rather than essential tremor. Therefore, we propose that indeterminate tremor should be considered as a separate clinical entity from essential tremor and that it might be dystonic in nature. Somatosensory temporal discrimination appears to be a useful tool in tremor classification. © 2019 International Parkinson and Movement Disorder Society